Politik Pendidikan Islam Paku Buwana X - Hermanu Joebagio (Millah: Journal of Religious Studies, 2005)
The kratons of Java were at times themselves leading agents of Islamisation. Sultan Agung's the great kings of Mataram dynastic has been reputation as reconciler of courtly culture and Islamic piety. Islamisation in Java has been stagnancy after the death of Sultan Agung, and continued centuries later by kings of Kasunanan, that is Sunan Paku Buwana (PBJ II, PB IV, PB VI, and PBX. This articles tries to analysis Islamic education politics in the reign of Sunan PBX. The background of Sunan's political thinking was to restored the power that has been disappeared by penetration of Dutch colonial The strategy to restored the power that is built Islamic School in 1905, named Madrasah Mambaul ‘Ulum. This madrasah consists of elementary school level (ibtidayah), secondary school level (tsanawiyah), and senior high school level (aliyah). For ibtidaiyah level expanded in seven regencies, i.e. Klaten, Boyolali, Kartosuro, Sukoharjo, Wonogiri, Sragen, and Surakarta. The expanded Ibtidaiyah level has been provoked revivalism and Islam solidarity, this phenomenon was exceptionally beneficial to the Sarekat Islam.